Apologie Pawel Fjodorowitsch Karamasows. Schuld bei Dostojewskij und seinen Interpreten - Paulin, Maximilian (Studia Gdańskie, 2013)
In a common interpretation of Dostoyevsky’s The Brothers Karamasov, Dmitri Kara‑ masov is held guilty of murdering his father in a moral sense, while the character of Smerdyakov is put beyond the range of ethic consideration as he is seen as an allegory of the merely executing factor of the act of violence. Hence, his suicide is read as a proof that the evil itself doesn’t take over responsibility; in face of the accusation it fades away, leaving the charge of responsibility to the human moral subject. Dostoyevsky, however, seems not wanting to stress such a kind of moral hero that, in this interpretation, could be seen in Dmitri. With introducing Alexey in his preamble, he is in fact presenting us a "weak" hero, leading us to another understanding of the story. Yet Alexey is still not the weakest. It is Smerdyakov. What this article pleads for is that Smerdyakov is systematically made a scapegoat, as Dostoyevsky is illustrating in several pertinent scenes. It is only coherent that interpreters, while completely ignoring this fact, contin‑ ue this scapegoating in dehumanising him by taking off him of all ethic consideration, reducing him to a personification of a merely mechanic component. By contrast, this is an apology for Smerdyakov as a human being. And as a son of Fyodor and brother of Alexey, Dmitri and Ivan.